Identifikasi Kerusakan Mesin Pada Sepeda Motor Menggunakan Metode Modified K-Nearest Neighbor (MKNN) - Adhiyatma Mugiprakoso; Nurul Hidayat; Marji Marji (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The transportation vehicle most used by the public today is motorcycles. According to data from the national statistics center, 81.5% of the transportation equipment used by the public is motorcycles from all transportation equipment in Indonesia. Motorcycles have advantages compared to other transportation equipment such as low maintenance costs, affordable prices, economical fuel and low maintenance costs. On motorcycles there can also be various problems with the engine which can interfere with driving comfort or even accidents. Many of the motorcycle riders have little knowledge of motor engine damage. Of the many classification methods that can be used to repair machine damage, one of them is the Modified K-Nearest Neighbor (MK-NN) method. The method studied the pattern of previous examination data based on symptoms of demage with eucledian distance calculation process, calculation of validity value and weighted voting calculation that the end result is used for class classification determination based on predetermined value of k. To identify damage to a motorcycle engine by using 9 types of damage with 13 symptoms and a total of 110 training data. The highest accuracy obtained from the test results was 86.67%.